ANALISIS PEMERIKSAAN PAJAK TERHADAP PENCAPAIAN TARGET PENERIMAAN PAJAK - Indan Jurina; Hadi Jauhari; Dewi Fadila (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2020)
This study aims to analyze how much the relationship between tax audits on the achievement of tax revenue targets at the Tax Office (KPP) Pratama Palembang Ilir Timur. Data were analyzed by quantitative descriptive method using SPSS Version 20 program. Types and sources of data used were primary data and secondary data obtained from the Tax Office (KPP) Pratama Palembang Ilir Timur, sampling in this study used a saturated sampling technique because of the population. in this study is relatively small, with a sample size of 30 people. Based on the results of data analysis carried out by the analysis technique on the classical assumption test, regression models are normally distributed, multicollinearity does not occur, heteroscedasticity does not occur and there is a correlation, the results are obtained simultaneously that the relationship between tax audits and the achievement of tax revenue targets is 42.8%. which means that the relationship between tax audit and the achievement of tax revenue targets is quite close and variations in changes in tax revenue achievement are influenced by tax audits. Meanwhile, the remaining 57.2% was influenced by other factors such as economic growth, inflation, the rupiah exchange rate and state spending.